Ketimpangan Regulasi dan Implementasi Penegakan Hukum Kasus Pencemaran Sumber Daya Air - Reyna Yuliza Mahmudah (Savana, 2025)
Law Number 17 of 2019 concerning Water Resources serves as the legal basis for the protection of water resources, which are part of human rights and environmental sustainability. Water resources, as a vital component of life, are utilized for various purposes, including in industrial sectors such as mining, thus triggering conflicts of interest and having a negative impact on the environment, such as the case of PT. Lematang Coal Lestari, which was charged with Article 79 of the Water Resources Law for carrying out construction without a permit. The purpose of this study is to evaluate the effectiveness of regulations and legal implementation related to water resources management in the case of pollution of the Penimur River by PT. Lematang Coal Lestari. Pollution caused by corporate activities without technical permits reflects the weak application of the principle of strict liability in environmental protection. The research method used is normative juridical with the approach of Lawrence M. Friedman's legal system theory, which involves an evaluation of the legal substance, legal structure, and legal culture that play a role in water resources management. The study concluded that despite the existence of legal frameworks such as Law No. 32 of 2009 concerning Environmental Protection and Management and Law No. 2020 concerning Mineral and Coal Mining, their implementation remains weak. The sanctions imposed, such as a Rp 2 billion fine on PT. LCL, have proven ineffective in deterring perpetrators, and environmental restoration is not included in the punishment. In conclusion, this case demonstrates the need for legal reform, including strengthening sanctions, enforcing individual responsibility, ecological restoration, and increasing public oversight and participation.